2016
DOI: 10.3390/polym8110397
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Imiquimod and Plasmid DNA via an Amphiphilic pH-Responsive Star Polymer that Forms Unimolecular Micelles in Water

Abstract: Dual functional unimolecular micelles based on a pH-responsive amphiphilic star polymer β-CD-(PLA-b-PDMAEMA-b-PEtOxMA) 21 have been developed for the co-delivery of imiquimod and plasmid DNA to dendritic cells. The star polymer with well-defined triblock arms was synthesized by combining activator regenerated by electron-transfer atom-transfer radical polymerization with ring-opening polymerization. Dissipative particle dynamics simulation showed that core-mesophere-shell-type unimolecular micelles could be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…These findings indicated that particle size of micelle/DNA complexes decreased gradually when the N/P ratio increased. Our results are compatible that increasing amount of cationic polymer caused more tight condensation with DNA that leads to small particles [1,24]. The largest particle size was observed at N/P ¼ 4 for PPP30 micelle/DNA complexes and at N/P ¼ 2 for PPP60 micelle/DNA complexes.…”
Section: Physicochemical Characterization Of Blank Micelles and Micelsupporting
confidence: 86%
“…These findings indicated that particle size of micelle/DNA complexes decreased gradually when the N/P ratio increased. Our results are compatible that increasing amount of cationic polymer caused more tight condensation with DNA that leads to small particles [1,24]. The largest particle size was observed at N/P ¼ 4 for PPP30 micelle/DNA complexes and at N/P ¼ 2 for PPP60 micelle/DNA complexes.…”
Section: Physicochemical Characterization Of Blank Micelles and Micelsupporting
confidence: 86%
“…Some typical signals include changes in temperature, irradiation with light, application of mechanical force, exposure to alternating electric or magnetic fields, and changes in chemical composition or pH of the external environment . In a parallel manner, recent advances in biomedicine have led to an increased interest toward controlled drug release which can be achieved with these star‐shaped polymer systems . Conventional methods of drug administration are nonspecific and they usually involve periodic application to the patients, raising the concentration of drug levels throughout the entire biological system.…”
Section: Introductionmentioning
confidence: 99%
“…β-cyclodextrin (CD) was also used as multivalent scaffold to build multi-arm block copolymers of poly-lactic acid (PLA), poly-2-(dimethylamino)ethyl methacrylate (PDMAEMA) and poly-oligo(2-ethyl-2-oxazoline)methacrylate (PEtOxMA) [78]. PDMAEMA, containing tertiary amines, made the polymers pH responsive.…”
Section: Unimolecular Micelles As Drug Delivery Systemsmentioning
confidence: 99%